Leadership and Organizational Culture in Islamic Schools: Implications for Educational Innovation - Nur Efendi (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2025)
This study investigates the relationship between leadership and organizational culture and its implications for educational innovation in an Islamic school context at MTsN Tulungagung. The study addresses how leadership shapes organizational culture, how culture influences innovation, and how both interact within institutional practices. A qualitative case study design was applied to explore experiences of the principal, teachers, and administrative staff. Data were collected through semi-structured interviews, observations, and document analysis, followed by thematic analysis. The findings show that leadership establishes a value-based organizational culture characterized by trust, collaboration, and continuous learning, which becomes a foundation for institutional practices. This culture encourages teachers to engage in reflective practice, experiment with instructional strategies, and integrate innovative approaches in teaching. Educational innovation is reflected in interactive learning methods, collaborative activities, and adaptive instructional design that respond to student needs. The study also reveals a cyclical relationship where leadership shapes culture, culture supports innovation, and innovation outcomes provide feedback that refines leadership strategies and institutional development.